Ongoing dual-angle measurements for the correction of partial saturation in 31P MR spectroscopy. - Tyler, D; Lopez, O; Cole, M; Carr, C; Stuckey, D; Lakatta, E; Clarke, K; Spencer, R (2010)
Use of a repetition time similar to, or shorter than, metabolite T(1)s is common in NMR spectroscopy of biological samples to improve the signal-to-noise ratio. Conventionally, the partial saturation that results from this is corrected using saturation factors. However, this can lead to erroneous results in the presence of chemical exchange or nonconstant T(1)s. We describe an alternative approach to correction for saturation, based on ongoing dual-angle T(1) measurement. Using (31)P magnetic resonance spectroscopy of the perfused rat heart undergoing ischemia-reperfusion, we demonstrate that signal alternations in the data acquired by the dual-angle approach are eliminated by the ongoing dual-angle T(1) measurement correction scheme, meaning that metabolite concentration and T(1) measurement can be made throughout the course of the ischemia-reperfusion protocol. Simulations, based on parameters pertinent to the perfused rat heart, demonstrate that accurate saturation correction is possible with this method except at times of rapid concentration change. Additionally, compared to the conventional saturation factor correction method, the ongoing dual-angle T(1) measurement correction scheme results in improved accuracy in determining the [phosphocreatine] recovery time constant. Thus, the ongoing dual-angle T(1) measurements procedure permits accurate monitoring of metabolite concentrations even in the setting of chemical exchange and T(1) changes and allows more accurate analysis of bioenergetic status.